Student Perceptions About The Personality Competence Of The Academic Advisor And Its Role In Helping Student Learning Success - Nora Novita; Mudjiran Mudjiran (Jurnal Neo Konseling, 2021)
Perception is a person's thought process in giving meaning to the stimulus he receives through the five senses that affect and assess the stimulus received by the subject, while role is an action or behavior performed by someone who occupies a position in social status. a series of rules that guide a person in social life. This study originated from the findings that there are still students who are afraid to meet their own Academic Advisors because they are easily emotional and are considered as a killer lecturer and there are students who think it is difficult to consult with academic advisors. This lesson aims to describe students' perceptions of the personality competence of the academic advisory lecturer and its role in helping student learning success. This research uses a descriptive approach with quantitative methods. The sample in this study was students of the Faculty of Education, State University of Padang with the 2017 and 2016 entry years totaling 97. The data collection tool used was a questionnaire. The data analysis technique used descriptive statistical analysis. The findings of this study as a whole show that students' perceptions of personality competence and academic advisory lecturers and their role in helping student learning success at the Faculty of Education, State University of Padang based on the attitude aspect are in the good category with a percentage of 51%, based on the action aspect is in the good category with the percentage of 49%, based on the aspect of speech, is in the good category with a percentage of 56%. Furthermore, the role of academic advisory lecturers based on academic aspects is in the very good category with a percentage of 48%, then the role of academic advisory lecturers based on non-academic aspects is in the very good category with a percentage of 44%.